COMPATIBILITY STUDY AND SUPPORTING CAPACITY OF TOURISM AT PERERENAN BEACH BADUNG, BALI - Vianthi, Ni Putu Yunita Laura; Widiastuti, Widiastuti (ASTONJADRO, 2021)
The challenge of Pererenan Beach Development is to determine the efficiency of resource utilization, so that it does not exceed its carrying capacity. The carrying capacity of Pererenan Beach tourism is carried out by analyzing the suitability of coastal tourism. Then calculate the capacity to measure the number of tourists that can be accommodated without damaging the ecosystem. This study aims to determine the suitability and carrying capacity of coastal tourism. The method used is quantitative and descriptive analysis method. The results showed that the carrying capacity of the area on Pererenan Beach was classified under the carrying capacity and had a very suitable relative criterion (S1) with a percentage value of 96% suitable for use as beach recreation tourism. The Covid-19 pandemic provides a lesson that the concept of carrying capacity is important to avoid mass tourism and reduce the number of tourists according to their capacity so that visitors get comfort and travel satisfaction.